Automated columnar microstructure analysis using CoCo (Column Counter): insights from EB-PVD TBCs - Almandoz Forcen, Koldo; Isern, Luis; Johnstone, Alan; Brewster, Gyaneshwara; Nicholls, John R.; Chalk, Christine (Elsevier, 2026)
Thermal barrier coatings (TBCs) are essential for protecting gas turbine components from extreme heat. The columnar microstructures produced by conventional electron beam physical vapour deposition (EB-PVD) provide pathways for the transport of heat and molten calcium–magnesium–alumino–silicates (CMAS), compromising their insulation capability and durability. Modifications to the columnar grain morphology have been shown to improve the performance and durability of EB-PVD TBCs, but replicable quantification of these key morphologic parameters remains elusive. In the present work, we present an automated method for the measurement of column width, Column Counter (CoCo). This method is applied to characterize a wide array of microstructures produced by systematically varying substrate temperature (430–1030 °C) and rotation speed (1–8 rpm). The wide spectrum of novel microstructures produced, ranging from columns with periodic porosity bands to layered architectures, markedly diverge from standard columnar TBCs. The morphological analysis is complemented by advanced characterization via X-ray diffraction (XRD) and electron backscattered diffraction (EBSD), revealing how the deposition parameters control column width, crystallographic texture strength and grain multiplicity within columns. Lower temperatures and slower rotations promote finer, less strongly textured coatings with reduced intercolumnar pathways. The results obtained through CoCo showcase the potential of automated morphological analysis in the tailored design of TBCs for improved performance and durability.
Keywords: 40 Engineering; Applied Physics; 4016 Materials engineering; 5104 Condensed matter physics; Image analysis; Microstructure; EBSD; Thermal barrier coatings; Electron-beam physical vapour deposition